The Effect of Political Configuration on the Implementation of Tasks and Authorities of the Corruption Eradication Commission (KPK) in Indonesia - Sugeng Dwiono; Erry Setia Negara; Azzahra Rizki Ananda (PT FORMOSA CENDEKIA GLOBAL, 2023)
was established on December 29, 2003, to enhance efforts to eradicate corruption in Indonesia. KPK has the task and authority to coordinate, supervise, investigate, prosecute, and prevent corruption, as well as monitor the administration of state governance. Since its establishment, KPK has handled over 1,064 corruption cases committed by public officials and individuals close to the seat of power. However, in carrying out its duties, KPK has encountered obstacles such as political configuration influences and limitations on authority through legislation. Therefore, this research aims to evaluate the influence of political configuration on the performance of KPK as well as the obstacles that hinder KPK from carrying out its duties and authority optimally.